FLEXIBILITY OF PRANG SABI VERSES: EVER-CHANGING ACEHNESE PERCEPTIONS OF HOLY WAR - Syukri Rizki Rizki (LIPI Press, 2020)
Verses of prang sabi (holy war) have been receiving various actualization throughout Aceh’s history. This paper investigates the flexible features of the authorship of prang sabi texts and their relation with the conceptualization of the idea of holy war in the Aceh society. The “flexible concept” proposed by Muhammad Haji Salleh (2018) serves as the framework on which the structure of the hikayat is unraveled. Library sources, both online and offline, provide the data for the analysis of how the idea of holy war varies in the Aceh society. Being designed with mixedmethod, the selected time frames of Aceh’s history are the times of the Dutch colonization, DI (Darul Islam) revolt, and GAM (Free Aceh Movement) insurgency. The findings reveal that the flexible concept in prang sabi texts rests on the sanjak system employed in the composition of Acehnese hikayats. This system allows improvisation for the texts to suit the contexts in which they are written. The idea of holy war to stand in the name of Islamic faith predominated during the Acehnese defense against the Dutch and of the DI’s and GAM’s revolts against the Indonesian statehood. All these movements claimed justification because the targets of the holy war were regarded as dangerous infidels (kaphé). Certain events served as the starting points of the three struggles. The Dutch annexation in 1873 marked the beginning of prang sabi against the Dutch, the abolishment of Aceh province followed by its incorporation into North Sumatera in 1951 triggered the prang sabi of DI against Indonesia, and the aspiration to separate Aceh as an independent Islamic state declared in 1976 marked the prang sabi of GAM against Indonesia. This study confirms that the flexible properties of prang sabi texts are responsible for the conceptualization of the idea of holy war in Aceh society.